METODE RISK PROFILE GOOD CORPORATE GOVERNANCE EARNING DAN CAPITAL (RGEC) UNTUK MENILAI TINGKAT KESEHATAN BANK PADA PT BANK RAKYAT INDONESIA Tbk - Lizvan Mangatur Sitorus (Politeknik Raflesia Press, 2021)
Abstract - This study aims to assess the soundness of the bank using the Risk Profile, Good Corporate Governance, Earning and Capital (RGEC) method for the 2018-2020 period. Based on the results of research, the health level of PT Bank Rakyat Indonesia Persero (Tbk) in 2018 to 2020 received a Composite Rating 1 (PK-1) which is